In House Training (IHT) dalam penyusunan karya tulis ilmiah - Hodiyanto Hodiyanto; A A Alimin (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2020)
One of the requirements in applying for teacher promotion is the publication of a scientific article. However, based on the results of interviews, many teachers have difficulty compiling scientific papers. Therefore, the Community Stimulus Partnership Program (CSPP), can help teachers prepare scientific papers through In House Training (IHT). This community service program aims to: 1) increase the knowledge of teachers in the preparation of proposals, reports, and writing scientific articles, especially Classroom Action Research (CAR), 2) determine the responses of training participants. The method used in this activity is workshops, training, seminars, mentoring, proposals seminars, and research results seminars. Meanwhile, determining the achievement of the activity results is through tests about the publication of a scientific article and a questionnaire on training participants' responses. The activity results showed: 1) increased knowledge of teachers in preparing proposals, reports, and scientific writing articles, 2) the level of participant satisfaction was 88%, which means that participants were delighted with this activity.